ANALISIS KEBIJAKAN PEMERINTAH PROVINSI SUMATERA BARAT DALAM PENANGANAN PENYANDANG DISABILITAS MENTAL ORANG DENGAN GANGGUAN JIWA - Syafrizal, Syafrizal (Universitas Fort De Kock, 2024)
The focus of this study is to evaluate the implementation of the Regional Regulation of West Sumatra Province regarding the protection and fulfillment of the rights of people with mental disabilities (ODGJ). The type of research used is qualitative research. The data sources used are primary sources, namely information sourced from direct observation of the research location by means of observation and interviews. While secondary sources are data obtained from documentation. data collection is carried out through observation, interviews, and documentation as well as data analysis with the stages of data reduction, data presentation, and drawing conclusions. The results of this study are that the policy regarding the handling of ODGJ already exists in the form of West Sumatra Governor Regulation Number 20 of 2016, internal resources in the form of funds, facilities and personnel already exist, facilities and infrastructure already exist but are still lacking, communication between organizations already exists, social environmental conditions are still bad, prevention and follow-up programs have been implemented.